Isolation of Partial Housekeeping Genes on Tuntun Angin (Elaeocarpus floribundu) - Dewi Indriyani Roslim; Ashfira Ashfira; Dilla Mutiarawati; Tio Fanny Rosmeilinda; Nur Aisyah; Herman Herman; Wahyu Lestari (Biosaintifika: Journal of Biology & Biology Education, 2019)
Some genes like 18S rRNA, 26S rRNA, elongation factor 1-alpha (EF1a), and beta-tubulin (TUB) are members of housekeeping genes group that are commonly used as internal control in gene expression study. This study aimed to isolate those four housekeeping genes of tuntun angin (Elaeocarpus floribundus). The research material included fresh leaves of E. floribundus that were picked up from Kajuik Lake in Riau Province and four primer pairs. The procedures consisted of total DNA isolation using Genomic DNA Mini Kit Plant (Geneaid), polymerase chain reaction (PCR), electrophoresis on 1% agarose gel, sequencing, and bioinformatic analysis. This study has been isolated 18S rRNA, 26S rRNA, EF1a, and TUB genes with the size of 422 bp, 922 bp, 856 bp, and 877 bp, respectively. The EF1a and TUB genes has never been reported in Elaeocarpaceae family. Thus, those partial DNA sequences are the first sequences reported from this species and can be used as reference genes in this plant after validation.